Compressive strength at high temperatures of a concrete made with recycled tire textile and steel fibers - Santos, C.C. (2014)
This paper presents the results of a research work on the evaluation of the compressive strength at high temperatures of a concrete made with recycled tire steel and textile fibers. It was considered five different concrete compositions, with a water/cement ratio (W/C = 0.43), differ only in the type and amount of fibers. The compositions with smaller amounts of textile fibers were those that gave better results. The compositions with steel fibers showed a less explosive rupture showing the effectiveness of this type of fibers in the spalling and cracking control.